BALANCING JUSTICE AND RIGHTS: THE INDIAN JUDICIARY’S APPROACH TO HUMAN RIGHTS PROTECTION - Arora, Girish; Shekhawat, Jitendra Singh; Sharma, Neha (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The Indian judiciary plays a pivotal role in interpreting and safeguarding human rights within the framework of the Indian Constitution. This paper explores the judiciary’s perception of human rights, focusing on its proactive approach in expanding the scope of fundamental rights and ensuring justice for marginalized communities. By examining landmark judgments, the study highlights the judiciary’s emphasis on the principles of equality, liberty, and dignity as enshrined in the Constitution. Additionally, it underscores the judiciary’s commitment to balancing individual rights with societal interests, often bridging gaps left by legislative and executive inaction. Despite challenges such as judicial overreach and delays, the judiciary’s evolving perception reflects its dedication to promoting justice and upholding human rights in a dynamic and diverse society. These abstract aims to provide insights into the judicial perspective, emphasizing its critical contribution to human rights jurisprudence in India.